Show that.

(i)

(ii)

(iii)

(iv)

(v)

(i) First Find the value of LHS

Using Identity (a + b) ^{2} = a^{2} + 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(i)

On Adding in eqn (i), we get

First Find the value of RHS

Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(i)

Therefore from eqn (i) and equ (ii) we found that LHS = RHS

(ii) First Find the value of LHS

Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(i)

On Adding in eqn (i), we get

First Find the value of RHS

Using Identity (a + b)^{2} = a^{2} + 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(ii)

Therefore from eqn (i) and equ (ii) we found that LHS = RHS

(iii) First Find the value of LHS

Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(i)

On Adding in eqn (i), we get

Therefore we found that LHS = RHS

(iv) First Find the value of LHS

Using Identity (a + b) ^{2} = a^{2} + 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(i)

Using Identity (a - b) ^{2} = a^{2} - 2ab + b^{2} for finding the value of

In the given expression a =

On substituting these values in the above identity, we get

⇒ ………………………………………………..(ii)

On subtracting eqn (ii) from eqn (i), we get

Therefore we found that LHS = RHS

(v) Using Identity (a + b)(a - b) = a^{2} - b^{2}

In the given expression a =

On substituting these values in the above identity, we get

……………………………………………………….(i)

On substituting these values in (b - c) (b + c), we get

……………………………………………………….(ii)

On substituting these values in (c - a) (c + a), we get

……………………………………………………….(iii)

On adding eqn (i), (ii) and (iii), we get

5